Current Problems of Training Pedagogical Staff for the Implementation of Inclusive Education (Eurasian Research Bulletin, 2022)
Inclusion primarily involves the inclusion of all children in society, because children with disabilities most of all need a friendly educational environment, which at the same time would not be artificial. Programs specially developed for "special" children are implemented in the isolation of boarding schools. Correctional organizations create a closed world for the child, in which attention is focused on his “lack”. An inclusive approach gives children the opportunity to become part of society and live a real life.